Wave propagation simulation based on the Fourier diffraction integral for X-ray refraction contrast imaging-computed tomography - Chang, Won-Seok; Kim, Jong-Ki; Cho, Jin-Ho; Lim, Jae-Hong (Journal of the Korean Physical Society, 2016)
With the advent of coherent X-ray sources, X-ray refraction has begun to be utilized for X-ray imaging of unprecedented sensitivity. The aim of this study was to develop a wave propagation simulator that provides a map of X-ray refraction after passing through an object. We applied the Fresnel diffraction integral for calculating the propagated wave and then obtained the refraction map by differentiating the phase in the refraction-analyzing direction. The simulation was validated by comparing the computed tomography (CT) reconstruction of a virtual phantom with its map of refractive index: the deviations were below 0.7% for soft tissues under our test condition. The simulator can be used for testing and developing highly-sensitive X-ray imaging techniques based on X-ray refraction analysis prior to experimentation.